TBVA-GAN: a class activation mapping-guided tuberculosis visual attribution generative adversarial network - Ding, Zeyu; Yaakob, Razali; Azman, Azreen; Mohd Rum, Siti Nurulain; Zakaria, Norfadhlina; Ahmad Nazri, Azree Shahril (Little Lion Scientific, 2023)
Visual attribution (VA) methods play a crucial role in tuberculosis (TB) research by providing valuable insights into disease patterns and aiding in diagnostic interpretation. The advent of generative adversarial network (GAN)-based VA methods has gained significant attention from researchers due to their ability to generate fine-grained feature maps that accurately reflect the location of lesions. These methods localize lesions by converting chest X-ray (CXR) images containing lesions into normal CXR images and analyzing the differences between the two. However, current methods only perform surface-level transformations, neglecting the vital information of whether lesions are present. Moreover, the transformation process assigns equal weights to the entire image, without specifically prioritizing the regions with a higher probability of lesions occurrence. In this study, a novel framework is proposed, namely the class activation mapping-guided tuberculosis visual attribution generative adversarial network (TBVA-GAN). This innovative model leverages the informative regions derived from class activation mapping to effectively guide the GAN in prioritizing the transformation of these crucial areas. Moreover, to guarantee the precision of TB localization, an auxiliary TB detection model is incorporated, ensuring that the converted CXR images are devoid of TB pathology. By employing this additional verification step, the accuracy of TB localization is significantly enhanced. The proposed TBVA-GAN in this study achieves promising VA results on the TBX11K dataset, surpassing existing GAN-based TB VA models.